Aerobic Biodegradation of OCDD by P. Mendocina NSYSU: Effectiveness and Gene Inducement Studies: Lin et al. (1st December 2017) - Lin, J. L.; Lin, W. C.; Liu, J. K.; Surampalli, R. Y.; Zhang, T. C.; Kao, C. M.
ABSTRACT: : The goals of this study were to assess the effectiveness of (1) enhancing octachlorinated dibenzo ‐p‐ dioxin (OCDD) biodegradation under aerobic conditions by Pseudomonas mendocina NSYSU ( P. mendocina NSYSU) with the addition of lecithin, and (2) inducing OCDD ring‐cleavage genes by pentachlorophenol (PCP) and OCDD addition. P. mendocina NSYSU could biodegrade OCDD via aerobic cometabolism and lecithin was used as a primary substrate. Approximately 74 and 67% of OCDD biodegradation was observed after 60 days of incubation with lecithin and glucose supplement, respectively. Lecithin was also used as the solubilization additive resulting in OCDD solubilization and enhanced bioavailability of OCDD to P. mendocina NSYSU. Two intradiol and extradiol ring‐cleavage dioxygenase genes (Pmen_0474 and Pmen_2526) were identified from gene analyses. Gene concentration was significantly enhanced after the inducement by PCP and OCDD. Higher gene inducement efficiency was obtained using PCP as the inducer, and Pmen_2526 played a more important role in OCDD biodegradation.